2011
DOI: 10.4028/www.scientific.net/amr.222.271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Red Luminescent Non Symmetric Styryl-4H-Pyran-4-Ylidene Fragment Containing Derivatives for Organic Light-Emitting Diodes

Abstract: New organic glassy non symmetric styryl- derivatives of 2(2,6-substituted-4H-pyran-4-ylidene)-malononitrile, 2(2,6-substituted-4H-pyran-4-ylidene)-1H-indene-1,3(2H)-dione and 2(2,6-substituted-4H-pyran-4-ylidene)-pyrimidine-2,4,6(1H,3H,5H)-trione were synthesized. They form thin solid amorphous films from volatile organic solvents (DCM and chloroform). Their spectral properties have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…We have synthesized fourteen (14) glassy organic compounds (see Fig.1) similar as reported in [4][5]8 . Obtained glassy organic compounds 1a-f, 2a-d and 3a-d could be grouped in three different classes with similar key molecular fragments: 1) 2,6-Bis-styrylsubstituted derivatives of 4H-pyran-4-ylidene with malononitrile as electron acceptor fragment (1a-f).…”
Section: Investigated Organic Compoundsmentioning
confidence: 96%
See 2 more Smart Citations
“…We have synthesized fourteen (14) glassy organic compounds (see Fig.1) similar as reported in [4][5]8 . Obtained glassy organic compounds 1a-f, 2a-d and 3a-d could be grouped in three different classes with similar key molecular fragments: 1) 2,6-Bis-styrylsubstituted derivatives of 4H-pyran-4-ylidene with malononitrile as electron acceptor fragment (1a-f).…”
Section: Investigated Organic Compoundsmentioning
confidence: 96%
“…In our previous researches 3- 6 we have shown that incorporated bulky triphenyl-groups in the structures of such organic molecules give them the ability to form thin amorphous solid films from volatile non-polar organic solvents. So far we have synthesized and investigated derivates of 6-methyl-2-styryl-4-pyran-4-ylidene 3,6 , 6-tert-butyl-2-styryl-4-pyran-4-ylidene 4,7 and symmetric 2,6-bis-styryl-4-pyran-4-ylidene 5 . Their photoluminescence spectrum in the solid state is in range from 600 to 800 nm and their glass transition temperature is in range from 100 o C to 160 o C [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds, which can make a solid-state glassy structure prepared from solutions, could facilitate technological processes in the production of many devices in optoelectronics, for example, light emitting devices by low-cost deposition such as wet casting methods and easier light-emitting material synthesis. Some of these red lightemitting compounds have been introduced by us [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach it is possible to obtain many different mono-styryl-substituted 4H-pyran-4-ones (compounds 17 in Fig.7). However only a few of previously synthesized compounds 17 give 2-styryl-substituted-6-methyl-4H-pyran-4-ones (compounds 18 in Fig.7) by acidic decarboxylation under the reaction conditions reported in [30,33] (see Fig.7) as summarised in Table 2 Yield -the practical production of the particular compound 17 in the reaction of dehydroacetic acid (compound 1 in Fig.6) with the corresponding aromatic aldehyde. M.p.…”
mentioning
confidence: 99%